Analysis of the 4C Model: Instagram Content Management Strategy of @Jabarsaberhoaks in Combating Hoaxes - Lathifah, Nisa; Dianova, Aulia; Noorlistyo Adi, Achwan; Lestari, Anggita; Christina Marbun, Dewi (Sinergi International Journal of Communication Sciences, 2024)
Hoaxes are fake news that are easily spread due to the fast flow of information and the high demand for social media. News fragments in online media that are not yet known in fact are the main trigger for the emergence of hoax news. The purpose of this research is to find out the implementation of social media utilization by @Jabarsaberhoaks in building public awareness of hoax news. This research uses qualitative methods and a case study approach. Primary data collection techniques are observation and interviews while secondary data are literature studies and documentation. There are three key informants from the @Jabarsaberhoaks account manager and two supporting informants from followers of the @Jabarsaberhoaks Instagram account. The data validity technique uses source triangulation. The results found that @Jabarsaberhoaks to build public awareness of hoax news is considered successful, namely by creating content according to the wishes of Instagram followers and collaborating with saber hoax units in West Java.